2014
DOI: 10.5539/ass.v10n12p41
|View full text |Cite
|
Sign up to set email alerts
|

Work Stress, Coping Strategies and Resilience: A Study among Working Females

Abstract: The aim of this review was to evaluate research relating to the effects of coping strategies and resilience on the level of workplace stress. Much of the research focused on working mothers and working females in general. It was found that working females experienced more work stress as compared to men. And currently in Malaysia, social policies that support working females, especially working mothers, has not been adopted fully by most corporations. Furthermore, the evidence for effective problem-focused and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…However, these different results supported to Kwok, Cheng, and Wong (2014) study, they had in fact argued that the results attained in Western countries may not be generalized to workers in other Asian countries, and other regions of the world (Spector et al, 2004). Hence, to date, studies on effective problem-focused and emotion-focused yielded inconsistent outcomes (Yi Lian & Lian Tam, 2014).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, these different results supported to Kwok, Cheng, and Wong (2014) study, they had in fact argued that the results attained in Western countries may not be generalized to workers in other Asian countries, and other regions of the world (Spector et al, 2004). Hence, to date, studies on effective problem-focused and emotion-focused yielded inconsistent outcomes (Yi Lian & Lian Tam, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, Torkelson and Muhonen (2008) found that men did not practice problemfocused individualistic coping strategies more often than women. Hence, to date, studies on effective problem-focused and emotion-focused coping yielded inconsistent results (Yi Lian & Lian Tam, 2014). Therefore, this study proposed the following hypotheses: Hypothesis 2: There is a significant relationship between problem-focused coping and WFC Hypothesis 3: There is a significant relationship between emotion-focused coping and WFC…”
Section: Coping Strategies and Wfcmentioning
confidence: 94%
See 2 more Smart Citations
“…Working mothers who perform two roles at the same time experience a higher level of stress. They are more exposed to various sources of stress, such as problems in their workplace or house or problems related to mother-child interaction (Lian & Tam, 2014).…”
Section: Discussionmentioning
confidence: 99%